MARKETING STRATEGY PLANNING FOR TAHU BAKSO IN MSMEs THROUGH THE MARKETING MIX FRAMEWORK AND TOPSIS - Putri, Ade Aisyah Arifna; Purwaningsih, Ratna; Afifah (Universitas 17 Agustus 1945 Semarang, 2025)
Micro, small, and medium-sized enterprises (MSMEs) producing tahu bakso face intense market competition and need efficient marketing strategies to maintain competitiveness. This study aims at developing strategy by identifyng criteria and selecting the optimal strategies. The research adopts the 4P marketing mix framework-product, price, place, and promotion-combined with the TOPSIS (Teqnique for Order Preference by Similarity to Ideal Solution) method. Five main criteria were identified: product price, retail location, product promotion, customer service quality, and product development. The weighting results show that produc price and customer service quality are the most importan factors, each with a weigh of 0.208. TOPSIS analisys indicates that stategy A8 - improving employee performance through targeted training and development-achieves the highest preference value. Improving employee performance is a strategyc priority, as it directly enhances service quality, customes satisfaction, and overall marketing effectiveness.